Using Motor Imagery to Access Alternative Attentional Strategies When Navigating Environmental Boundaries to Prevent Freezing of Gait – A Perspective - How, Daniella; Wagner, Heiko; Brach, Michael (Frontiers in Human Neuroscience, 2022)
Freezing of gait can cause reduced independence and quality of life for many with Parkinson’s disease. Episodes frequently occur at points of transition such as navigating a doorway. Therapeutic interventions, i.e. drugs and exercise, do not always successfully mitigate episodes. There are several different, but not exclusive causes for freezing of gait. People with freezing of gait are able to navigate dynamic situations like stairways by utilizing a different attentional strategy to over-ground walking, but may freeze when passing through a doorway. The question is, is it possible to employ a special attentional strategy to prevent freezing at this point? Motor imagery allows for learning motor skills in absolute safety and has been widely employed in a variety of populations, including other neuro-compromised groups. Motor imagery is not studied in a homologous manner in people with Parkinson’s Disease, leading to conflicting results, but may have the potential to establish a different attentional strategy which allows a subject to mitigate freezing of gait episodes. This paper will identify and discuss the questions that still need to be answered in order to consider this approach i.e. can this population access motor imagery, can motor imagery alter the attentional strategy employed when moving through doorways, what is the best motor imagery approach for people with Parkinson’s Disease and freezing of gait, and what dosage is most effective, while briefly outlining future research considerations.